In vitro strategies for mimicking dynamic cell–ECM reciprocity in 3D culture models - Urciuolo, F.; Imparato, G.; Netti, P. A. (Frontiers in Bioengineering and Biotechnology, 2023)
The extracellular microenvironment regulates cell decisions through the accurate presentation at the cell surface of complex array of biochemical and biophysical signals that is mediated by the structure and composition of the extracellular matrix (ECM). On the other hand, cells can actively remodel the ECM which in turn affects cell functions. This cell-ECM dynamic reciprocity is central in regulating and controlling morphogenetic and histogenetic processes. Misregulation within the extracellular space can cause aberrant bidirectional interactions between cells and ECM resulting in dysfunctional tissues and pathological states. Therefore, tissue engineering approaches, aiming at reproducing organs and tissues in vitro, should realistically recapitulate the native cell-microenvironment crosstalk that is central for the correct functionality of the tissue engineered constructs. In this review we will describe the most updated bioengineering approaches to recapitulate the native cell microenvironment and reproduce functional tissue and organ in vitro. We highlighted the limitations of the use of exogenous scaffold in recapitulating the regulatory/instructive and signal repository role of cell native microenvironment. In contrast, strategies to reproduce human tissues and organs by inducing cells to synthetize their own ECM acting as provisional scaffold to control and guide further tissue development and maturation hold the potential to allow the engineering of fully functional histological competent three-dimensional (3D) tissues.